Embarrassed customers: the dark side of receiving help from others - Kim, Seo Young; Yi, Youjae (International journal of service industry management, 2017)
Purpose The purpose of this paper is to demonstrate that customer engagement behavior may not always be a positive experience for customers. Specifically, the paper examines the effect of sources of help (employee vs customer) on customer satisfaction, and the underlying mechanism behind such an effect. Design/methodology/approach Three studies were conducted to test the hypotheses, and bootstrapping was used to analyze the proposed mediation and moderation models. Findings The results from the studies demonstrated the effect of sources of help (employee vs customer) on customer satisfaction. Specifically, compared to those who have received help from employees, customers who have received help from other customers showed lower satisfaction toward the firm. The relationship between sources of help and satisfaction was mediated by an affective factor, embarrassment, and a cognitive factor, altruistic motivation. In addition, the relationship between embarrassment and satisfaction was moderated by concern for face. Practical implications Firms should devote more resources toward minimizing customers’ embarrassment during service encounters and demonstrate altruistic motivation to provide voluntary help to lead customers to reciprocate helping. Originality/value The current research provides a new perspective on customer engagement behavior during service encounters. This research highlights the negative outcomes of receiving help from other customers.